Um estudo comparativo de VoIP (voz sobre IP) com a telefonia convencional no Brasil - Tancon, Marcos Antonio (2018)
Due to technological advances, the networks have been undergoing enormous changes and supporting more and more new services, as is the case of services based on VoIP (voice over IP). To support telecommunications services, performance and reliability assurance are required, where network protocols are responsible for meeting this requirement. Thus, it was opportune to carry out a study analyzing several performance factors of voice over IP communications, as well as operational and structural costs, and comparing them with conventional telephony in Brazil.